Development of Textbook Borrowing System Using Web-based Approach - LIAW, WAN QING; Mahdin, Hairulnizam (Applied Information Technology And Computer Science, 2024)
The Textbook Loan Scheme Program (SPBT) in Malaysia has provided educational resources since 1975. At SMK Bekok, the manual textbook management system, overseen by Coordinator Teacher Miss Pang, results in inefficiencies, inaccuracies, and tracking challenges. To address these issues, a modern Textbook Borrowing System is proposed to streamline processes, ensure accurate record-keeping, and enable real-time tracking. Utilizing the Waterfall Model of the Software Development Life Cycle (SDLC), the project follows a structured approach through planning, analysis, design, implementation, testing, and maintenance phases. The expected outcome is a web-based system that automates manual processes, enhances record accuracy, and simplifies borrowing and returning textbooks, ultimately creating a more efficient and conducive learning environment for SMK Bekok students.